Epidemiology of bus fires in mainland China from 2006 to 2015. Issue 4 (June 2018) - Liu, Yong; Wu, Pan; Ho, Jon Kee; Hua, Haiping; Chen, Haojiao; Cen, Ying; Guo, Songxue; Han, Chunmao; Wang, Xingang
Abstract: Objective: This study analyses the epidemiological characteristics of bus fires in mainland China over the past 10 years to develop prevention strategies and emergency procedures for such incidence and the resulting casualties. Methods: We collected reports on bus fires from the media and news websites and looked up on Medline, PubMed, and Chinese National Knowledge Infrastructure databases for relevant publications in English or Chinese from January 1, 2006 to December 31, 2015. Results: In the past 10 years, there were 382 bus fires in mainland China. The frequency of fires was markedly higher in 2013 and 2014. The vast majority (89.1%) of the fires were caused by spontaneous combustion, followed by arson (5.0%). There were reports of casualties in 41 (10.7%) of the bus fires, including 144 deaths and 567 injuries. The fires leading to casualties resulted from spontaneous combustion in 22 (53.7%) incidents, arson in 12 (29.3%) incidents, and traffic accidents in 7 (17.1%) incidents. Arson caused the most casualties, including 91 deaths and 323 injuries. Conclusions: This epidemiological study presents characteristic findings related to bus fires in China mainland. The general trend of bus fires showed a gradual increase but with a fluctuation in several years. The regional distribution of bus fires revealed some specific characteristics, and most of bus fires happened in those regions locating in the eastern area of China mainland. The largest number of bus fires were caused by spontaneous combustion. Bus fires caused by arson accounting for only 5% of the total bus fires resulted in the most severe casualties. Most of bus arson occurred in the morning and evening rush hours.